(untitled) (Global Journal of Human-Social Science, 2017)
Various scholarly articles have focused on interest rate effect on bank lending rate but not many have seen monetary policy as a wholesome factor that determines bank lending behaviour This study appraises the impact of monetary policy on commercial banks lending behaviour in Nigeria The Keynesian model which incorporated the role of money supply as a yardstick for interest rate to induce the public to hold additional money balances was adapted to investigate the link between monetary policies and commercial banks lending rate in Nigeria Annual time series data was sourced from the Central Bank of Nigeria s Statistical Bulletin between 1980 to 2014 Ordinary least square method OLS augmented dickey fuller test ADF co-integration test and Error correction model ECM were employed as estimation techniques